The potential transportation effects of transformation of traditional markets into modern malls: a case study of Mall Dinoyo City in Indonesia - Khan, Asif; Putro, Otafianto (AESOP, 2016)
The relationship between land use and transportation is well established. Commercial land uses can generate variable amount of traffic depending on its type and scale. For the past few decades it has been a trend in the western world to gradually upgrade the traditional markets to modern malls. Indonesia and some other Asian countries are following this trend and have recently taken steps for transformation of the shopping centres in the major cities. While the transformation is useful in lifting the image of the city and making it comparable with other major cities of the world, overlooking of local contexts and impacts of the development may lead to transportation issues. In some cities, such as Malang in Indonesia, it seems the transformation is taking place at a rapid pace without consideration for the consequences on the traffic and parking on the surrounding road network. More than 27 shopping centres in Malang have been identified for upgradation in the next few years. Out of which, two are complete, including the Dinoyo traditional market. In this paper we will study the development of this market and identify the transportation and associated issues. The main objectives of this paper are to investigate whether there were any limitations in the planning and development of the Mall Dinoyo City through the upgradation of Dinoyo traditional market, and identify the potential transportation effects of the transformation.
Proceedings of the IV World Planning Schools Congress, July 3-8th, 2016 : Global crisis, planning and challenges to spatial justice in the north and in the south